2020
DOI: 10.1111/1541-4337.12609
|View full text |Cite
|
Sign up to set email alerts
|

Why for feed and not for human consumption? The black soldier fly larvae

Abstract: With the surge in consumption of insects, the search continues to find ways to increase the popularity of insect‐based products in the Western world. The black soldier fly larvae (BSFL), which is mainly utilized for animal feed, has great potential to provide a sustainable source of nutrients for human food. This review aims to discuss some of the key benefits and challenges of BSFL and their potential role as a food ingredient and/or product for human consumption. Few articles specifically discuss BSFL as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 116 publications
(222 reference statements)
0
67
0
2
Order By: Relevance
“…A valuable and more sustainable source of protein is represented by insects. They have a high nutritional value [3][4][5] and, compared with traditionally farmed animals, insects have a much higher conversion efficiency and require much less water [2], and their rearing involves much less greenhouse gas emissions [6].…”
Section: Introductionmentioning
confidence: 99%
“…A valuable and more sustainable source of protein is represented by insects. They have a high nutritional value [3][4][5] and, compared with traditionally farmed animals, insects have a much higher conversion efficiency and require much less water [2], and their rearing involves much less greenhouse gas emissions [6].…”
Section: Introductionmentioning
confidence: 99%
“…Black soldier fly larvae (BSFL) hold the promise of being a sustainable, nutritious, economically viable food source, however, there are still some challenges that lay ahead before BSFL could be considered a sufficiently safe food source for human consumption [1]. One study has indicated consumers' willingness to consume BSFL in a processed form [2], but the food safety elements of BSFL remain largely unknown, since BSFL have been used almost exclusively for animal feed purposes.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, heating even caused proteins to have more of an allergic reaction [29]. Once again, this information calls for further validation through a wider body of research into BSFL allergens for safe human consumption [1].…”
Section: Introductionmentioning
confidence: 99%
“…However, evaluation of their utilization in ruminant diets is still limited to date which is related to the potential risk of mad cow disease (Bovine Spongiform Encephalopathy). The European Union regulations prohibit the use of processed animal protein to feed food-producing animals [ 27 ]. The European Union allows the usage of insect as a feed in aquaculture since July 2017, with a recent approval from the European parliament and Council, and the Standing Committee on Plants, Animals, Food and Feed in April 2021 for the usage of insects to feed poultry and pig [ 28 ].…”
Section: Introductionmentioning
confidence: 99%